2017
DOI: 10.18203/2320-6012.ijrms20174548
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, pathophysiology, diagnosis and management of diabetics’ foot ulcer

Abstract: Diabetic foot ulcers (DFU) is a lesion of all layers of skin, necrosis or gangrene that occurs in the soles of the feet in diabetes mellitus (DM) patients, caused by: (1) causative factor (peripheral neuropathy, high foot plantar pressure and trauma); (2) contributive factors (atherosclerosis and diabetes). The treatments of diabetic ulcers consist of determining and repairing the underlying cause of ulcer, good wound care and prevention of ulcer recurrence. The cause of diabetic ulcers can be determined by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 21 publications
(31 reference statements)
0
45
0
9
Order By: Relevance
“…Previous studies such as Iraj et al and Rosyid et al also recognize this risk. 22,23 The finding that 78% of the study subjects were on injectable insulin is predictable as the duration of diabetes is directly linked to use of insulin and the risk of DFU.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies such as Iraj et al and Rosyid et al also recognize this risk. 22,23 The finding that 78% of the study subjects were on injectable insulin is predictable as the duration of diabetes is directly linked to use of insulin and the risk of DFU.…”
Section: Discussionmentioning
confidence: 98%
“…Incidences of DFU continue to increase worldwide [8]. The prevalence of DFU is not accurately known and the difference in prevalence rates in each country is estimated at 4-27% of DFU sufferers worldwide [9]. The lifetime risk of foot ulcers until recently was generally believed to be 15-25%; however, recent data suggest that the figure may be as high as 34% [10].…”
Section: Epidemiology Of Diabetic Foot Ulcersmentioning
confidence: 99%
“…The lifetime risk of foot ulcers until recently was generally believed to be 15-25%; however, recent data suggest that the figure may be as high as 34% [10]. Studies have shown that 15% of patients with DM will experience complications of DFU in the future [9].…”
Section: Epidemiology Of Diabetic Foot Ulcersmentioning
confidence: 99%
See 2 more Smart Citations